2019
DOI: 10.7717/peerj.7268
|View full text |Cite
|
Sign up to set email alerts
|

Towards sex identification of Asian Palmyra palm (Borassus flabelliferL.) by DNA fingerprinting, suppression subtractive hybridization andde novotranscriptome sequencing

Abstract: BackgroundAsian Palmyra palm, the source of palm-sugar, is dioecious with a long juvenile period requiring at least 12 years to reach its maturity. To date, there is no reliable molecular marker for identifying sexes before the first bloom, limiting crop designs and utilization. We aimed to identify sex-linked markers for this palm using PCR-based DNA fingerprinting, suppression subtractive hybridization (SSH) and transcriptome sequencing.MethodsDNA fingerprints were generated between males and females based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In previous studies, galactose metabolism was indicated to be linked to pistil abortion, and pistil deletion of Prunus mume and Camellia sinensis ( Shi et al, 2012 ; Liu et al, 2020 ). Also, galactose metabolism appeared to differ starkly between the male and female inflorescences of Borassus flabellifer palm ( Pipatchartlearnwong et al, 2019 ). 3-ketoacyl-ACP synthase (KAS III) and alpha-galactosidase which participate in the galactose metabolism pathway were specifically expressed in male flowers of Vernicia fordii ( Mao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, galactose metabolism was indicated to be linked to pistil abortion, and pistil deletion of Prunus mume and Camellia sinensis ( Shi et al, 2012 ; Liu et al, 2020 ). Also, galactose metabolism appeared to differ starkly between the male and female inflorescences of Borassus flabellifer palm ( Pipatchartlearnwong et al, 2019 ). 3-ketoacyl-ACP synthase (KAS III) and alpha-galactosidase which participate in the galactose metabolism pathway were specifically expressed in male flowers of Vernicia fordii ( Mao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only the female plant produces the edible by products, such as immature endosperm, matured fleshy mesocarp, and tuberous seedling (Vengaiah et al, 2017). However the male plant's inflorescence is used to harvest the delicious sap (Bondya & Bodra, 2014;Pipatchartlearnwong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The plant is dioecious while the flowering and fruiting occurs usually from March to April every year. The edible products like immature endosperm, mesocarp pulp, and tuberous seedling are obtained only from the female plant [3], while the sweet sap is extracted from the inflorescence of the male plant [4,5]. The tree usually thrives in tropical and subtropical regions of the world [5,6].…”
Section: Introduction mentioning
confidence: 99%
“…The edible products like immature endosperm, mesocarp pulp, and tuberous seedling are obtained only from the female plant [3], while the sweet sap is extracted from the inflorescence of the male plant [4,5]. The tree usually thrives in tropical and subtropical regions of the world [5,6]. Archeological and historical evidence indicated the presence of Borassus flabellifer L. in Southeast Asia dating back at least 1500 years.…”
Section: Introduction mentioning
confidence: 99%